Left global dimensions and inverse polynomial modules - Sangwon Park (International Journal of Mathematics and Mathematical Sciences)
We prove the fact l.gl.dimR[x]=(l.gl.dimR)+1, where l.gl.dim means the left global dimension by using inverse polynomial modules and injective dimensions. The classical way to prove the fact l.gl.dimR[x]=(l.gl.dimR)+1 is using polynomial modules and projective dimensions.